Elements of Management in the Face of Conflicts, Crises, Pandemics and Human Migration - Jerzy WACHOL (Communications of International Proceedings, 2022)
The study presents the functioning of world’s economy in the 21st century, taking into consideration the external environment, a threat of armed conflicts, as well as changes in technology, IT, economy and society. Included economic crises and today’s pandemic. Presented and discussed are worldwide economic and social data, where because of the pandemic visible are internal differences, economic and political problems. After a sudden fall in the GDP dynamics worldwide in 2020, chiefly due to the pandemic, it turned out that in 2021 the economies worldwide started to grow. However, the armed conflict in Ukraine at the beginning of 2022 and any sanctions related thereto, increased prices of energy and of raw materials may lead the world to another economic crisis, or even to World War III. The study is aimed at presenting some selected issues related to the management, functioning of economy in the face of economic crises, pandemics, armed conflicts and human migration. On this background presented were some selected management elements under own survey research. It turned out that nowadays, in the enterprises an important role is played by marketing, finances, profit, strategies, staff, innovation, modern management concepts; nevertheless, the fear of people and staff for a war breaks through, too. Anyway, no warfare should serve for solving social, economic and political crises. Basing upon the collected statistical data, own investigations, observations and literature some conclusions were formulated concerning the selected management elements and human migrations in the past and today.
Keywords: management elements; economic crisis; pandemic; human migrations; armed conflicts; globalization; management concepts.